TIRAKAT GURU NGAJI PONDOK MODERN DARUSSALAM GONTOR (STUDI DESKRIPTIF NILAI TEOLOGIS PONDOK PESANTREN GONTOR) - Siti Nurhaliza; Dina Amara Chasna; Muhammad Badrun Shahir; Alifah Yasmin; Zeny Luthvia; Dzatu Aliviatin Nuha (Jurnal Studi Pesantren, 2026)
Islamic boarding schools (pesantren) are Islamic educational institutions characterized by the central role of the kyai (Islamic scholar) and the mosque as the spiritual and educational center. Established upon a well-structured system and value framework, these institutions strive to cultivate the character of the nation and its people, particularly exemplified by Pondok Modern Darussalam Gontor. The term pesantren carries diverse meanings, both individually and collectively, among Muslim communities. It is closely associated with teachers (guru ngaji) and students (santri) who engage in the study of the Qur'an, classical Islamic texts, social and natural sciences, as well as various forms of learning beyond the classroom. Pondok Modern Darussalam Gontor has developed a distinctive concept and implementation in nurturing and shaping its community, encompassing not only students but also teachers and educational staff. This educational legacy has enabled Pondok Modern Darussalam Gontor to preserve its educational system for nearly a century. The findings are expected to broaden perspectives on the common stereotypes surrounding the tirakat tradition of guru ngaji in Islamic boarding schools, particularly at Pondok Modern Darussalam Gontor. The results of this study provide a descriptive and analytical account of the metaphysical spirit underlying the tirakat of guru ngaji at Pondok Modern Darussalam Gontor. This spirit is manifested not only in religious practices but also in the teaching of science, the development of mental resilience and character, the cultivation of collective consciousness, and the formation of dedicated and resilient Muslim educators. This study is expected to broaden public understanding of Islamic boarding schools, demonstrating that they are not merely religious educational institutions but also centers for nurturing individuals of noble character who contribute significantly to society, the nation, and the state.